Bloodstream infection catheter-related: a literature review - Tigulini, Regiane Souza; Angelieri, Daniela Bicudo (Revista de Enfermagem UFPE on line, 2011)
ABSTRACT Objective: to conduct a survey of the issues about primary bloodstream infection related to the central venous catheter (CR-BSI), published from 2000 to 2010. Method: literature search based on the databases Lilacs and Medline. Results: of the 47 articles researched, the highest number of publication occurred in 2007: 23.4% in 2010, 10.63% in 2009, 17% in 2008 and 14.9% in 2007. Brazil was the second country to publish the most number of researches in this matter (21.27%). In these publications, 48.93% evaluated the impact on the prevention of RC-BSI; 36.17% discussed about the epidemiology, risk factors and mortality rate; and 14.9% dealt with the description of recommended preventive measures, diagnosis and/or treatment. It wasn’t found, among these issues, any work that effectively evaluated the indicators of care processes. Conclusion: based on the increasing interest in learning the process of this infection and the expressiveness of the Brazilian publications added to the recommendations of the Brazilian National Health Surveillance Agency (ANVISA) on the process analysis with the aim of the introduction of a more assertive program to reduce this infection, it is suggested the need of a ceaseless search for new knowledge to ease the problems of prevention and control of RC-BSI. Descriptors: infection control; catheter-related infections; health care quality indicators. RESUMO Objetivo: realizar um levantamento das publicações produzidas no período de 2000 a 2010 acerca das infecções primárias de corrente sanguínea relacionadas ao cateter central. Método: pesquisa bibliográfica às bases de dados Lilacs e Medline. Resultados: dos 47 artigos encontrados, a maior produção deu-se a partir de 2007: 23,4% em 2010, 10,63% em 2009, 17% em 2008, 14,9% em 2007. O Brasil foi o segundo país a publicar maior número de trabalhos sobre o assunto (21,27%). 48,93% das publicações avaliaram o impacto de intervenções na prevenção das IPCS-RC, 36,17% discorreram sobre a epidemiologia, fatores de risco e mortalidade e 14,9% enfocaram a descrição de recomendações de medidas preventivas, diagnóstico e/ou tratamento. Dentre a seleção não foram encontrados trabalhos avaliando efetivamente indicadores de processos assistenciais. Conclusão: o crescente aumento no interesse em conhecer o processo destas infecções, diante da expressividade de publicações brasileiras somada às recomendações da ANVISA sobre análise de processos, objetivando implantar programas de redução de infecção mais assertivos, aponta a necessidade em manter a busca constante por novos conhecimentos impactantes no problema do controle e prevenção das IPCS-RC. Descritores: controle de infecções; infecções relacionadas a cateter; indicadores de qualidade em assistência à saúde. RESUMEN Objetivo: realizar una evaluación sobre las publicaciones de las infecciones primarias a cabo en el torrente sanguíneo relacionadas con el catéter central. Estas publicaciones son del periodo 2000 a 2010. Método: este documento se basa en los datos de LILACS y MEDLINE. Resultados: de cuarenta y siete (47) artículos de investigación, la mayoría de la producción de las infecciones ocurrió por primera vez en 2007: 23,4% en 2010, 10,63% en 2009, el 17% en 2008 y 14,9% en 2007. Brasil fue el segundo país de publicar el mayor número de investigaciones en esta materia (21,27%). En estas publicaciones, 48,93% estimó que el impacto en la prevención de IPCS-RC, 36,17% calificó la epidemia y sus tratamientos, los factores de riesgo y la mortalidad, y un 14,9% frente a la descripción de las recomendaciones de los métodos preventivos de diagnóstico y / o tratamientos. No se encontró, en esta selección, los trabajos efectivamente evaluar el indicador de proceso del asistente. Conclusión: el aumento del interés de conocer el proceso de estas infecciones, las publicaciones brasileñas y con las recomendaciones de la ANVISA sobre el proceso de análisis para el objetivo de la creación de programas en la reducción de estas infecciones muestra la necesidad de continuar la búsqueda de nuevos conocimientos en problemas de prevención y control de IPCS-RC. Descriptores: control de las infecciones; las infecciones relacionadas con cateter; los indicadores de calidad en la asistencia sanitaria.